2002
DOI: 10.1159/000063847
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Penetrating Keratoplasty in Rheumatoid Arthritis

Abstract: Background: Keratolysis in rheumatoid arthritis is a well-known disorder that may rapidly destroy the entire corneal stroma, resulting in descemetocele formation and eventually corneal perforation. The purpose of this study was to determine the anatomical and functional results of therapeutic penetrating keratoplasty (PK) in these patients. Patients and Methods: We reviewed the charts of patients having undergone PK over a 5-year period and evaluated the outcome. In 16 eyes of 15 patients, PKs were performed (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
6

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 18 publications
1
15
0
6
Order By: Relevance
“…Pour Killingsworth et al [3], le foyer infectieux est retiré dans la plupart des cas et l'utilisation de corticoïdes locaux semble justifiée sur de tels yeux enflammés. Par ailleurs, l'utilisation de collyre à la ciclosporine 2 % a montré son efficacité dans les greffes réalisées « à chaud » sur terrain de polyarthrite rhumatoïde [20].…”
Section: Discussionunclassified
“…Pour Killingsworth et al [3], le foyer infectieux est retiré dans la plupart des cas et l'utilisation de corticoïdes locaux semble justifiée sur de tels yeux enflammés. Par ailleurs, l'utilisation de collyre à la ciclosporine 2 % a montré son efficacité dans les greffes réalisées « à chaud » sur terrain de polyarthrite rhumatoïde [20].…”
Section: Discussionunclassified
“…24 The transparent or almost entirely transparent corneas in 82% of the eyes was better score than the reported outcomes of urgent keratoplasty or keratoplasty performed in dry eye. 25,26 Deterioration is expected to occur over time, however, because in severe dry eye, despite maximal management with tears, the prognosis for graft survival is not good. The poor prognosis also results from a lack of nutritional and growth factors contained in normal tears that are essential for proper limbal stem cell function.…”
Section: Discussionmentioning
confidence: 99%
“…In an (uncontrolled) study on patients with rheumatoid arthritis, topical CsA ointment showed a favourable effect on preventing corneal remelting [25]. However, the value of topical CsA for the prevention of graft rejection clinically remains unclear, because the results of different studies are contradictory [26, 27].…”
Section: Cyclosporin Amentioning
confidence: 99%